The relationship between coronary risk factors and elevated 1‐h postload plasma glucose levels in patients with established coronary heart disease. (11th December 2012) - Wu, Xing; Chen, Hui; Wang, Yongliang; Li, Hongwei
Summary: Objective: Recent studies have shown that an elevated 1‐h postload plasma glucose (1hPG) is able to identify subjects with normal glucose tolerance (NGT) at high risk for future type 2 diabetes and atherosclerotic cardiovascular disease. However, clinical studies about the characteristics of coronary heart disease (CHD) patients with elevated 1hPG are lacking. The aim of this study was to analyse the 1hPG level in CHD patients with NGT. Methods: A total of 204 CHD patients with NGT were recruited. Subjects underwent an oral glucose tolerance test, echocardiography and coronary angiography. Demographic data were recorded and blood samples obtained. According to the 1hPG cut‐off point of 8·6 mm, patients were divided into two groups: 1hPG ≥ 8·6 mm ( n = 65) and 1hPG < 8·6 mm ( n = 139). Results: Compared with the 1hPG < 8·6 mm group, subjects with 1hPG ≥ 8·6 mm had a worse metabolic profile, exhibiting significantly higher body mass index, systolic blood pressure, triglyceride level and lower HDL‐cholesterol level. Plasma high‐sensitivity CRP (hsCRP) levels were higher in the 1hPG ≥ 8·6 mm group than in the 1hPG < 8·6 mm group. Coronary angiography revealed that single‐vessel changes were more frequent in the 1hPG < 8·6 mm group, but there were no significant differences in the Gensini score. Conclusions: Patients with CHD with 1hPG ≥ 8·6 mm have a worse metabolic profile, higher levels of hsCRP and multi‐vessel coronary atherosclerosis. These findings suggest that, in patients with CHD, elevated 1hPG increases coronary risk factors and may be a marker for early‐stage glucose intolerance.